Analysis of Calorific Value of Biopellet Diameter Variations through Proximate Test - Asrianti, Nadia Putri; Fahrudin, Fahrudin; Rhakasywi, Damora; Martana, Budhi (Journal La Multiapp, 2024)
This study aims to evaluate the quality of biopellets as biomass energy fuel, focusing on physical and chemical characteristics based on the SNI 8021:2014 standard. The research method used is experimental with a non-factorial Completely Randomized Design (CRD). The raw materials used are a mixture of rambutan wood waste (Nephelium lappaceum L) and bintaro (Cerbera manghas) with tapioca flour as an organic binder. Testing includes proximate analysis (moisture, ash, volatile matter, and fixed carbon) and calorific value using an oxygen bomb calorimeter. The results show that the produced biopellets meet several parameters of the SNI 8021:2014 standard, such as moisture content, volatile matter, and fixed carbon. However, there is significant variation in ash test results among different diameters of biopellets tested. ANOVA test results indicate that mold diameter has a notation that has a significantly affect several biopellet characteristics, such as density and calorific value. This study also observed the potential for increased combustion efficiency of the produced biopellets. The results indicate that the raw material mixture used can reduce pollutant emissions during combustion. The conclusion of this study is that the use of a mixture of rambutan wood waste and bintaro with tapioca flour as an organic binder can produce biopellets with quality that meets standards for biomass energy applications.